2012
DOI: 10.1128/jb.00079-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of the Shrimp Pathogen Vibrio harveyi CAIM 1792

Abstract: Vibrio harveyi is a Gram-negative bacterium found in tropical and temperate marine environments as a free-living organism or in association with aquatic animals. We report the first sequenced genome of a Vibrio harveyi strain, CAIM 1792, the etiologic agent of the “bright red” syndrome of the Pacific white shrimp Litopenaeus vannamei .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The genome of this strain has been sequenced (Espinoza-Valles et al, 2012), and it is now possible to use bioinformatics tools to identify unique and shared genes among strains of this species and of phylogenetically closely related species. In this study, whole-genome sequences of strains of the closely related species V. harveyi, V. owensii, V. rotiferianus and V. campbellii were compared to the V. harveyi CAIM 1792 genome sequence to reveal the conservation level of genes between these strains and species.…”
Section: Introductionmentioning
confidence: 99%
“…The genome of this strain has been sequenced (Espinoza-Valles et al, 2012), and it is now possible to use bioinformatics tools to identify unique and shared genes among strains of this species and of phylogenetically closely related species. In this study, whole-genome sequences of strains of the closely related species V. harveyi, V. owensii, V. rotiferianus and V. campbellii were compared to the V. harveyi CAIM 1792 genome sequence to reveal the conservation level of genes between these strains and species.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not find the anguibactin cluster in the draft genome sequence of V. harveyi CAIM 1792 (Espinoza‐Valles et al. ). Lin et al.…”
Section: Resultsmentioning
confidence: 67%
“…The T4SS is responsible for the transport of virulent proteins or DNA into eukaryotic cells as well as for the conjugative transfer of plasmids from one bacterium to another ( Fronzes, Christie & Waksman, 2009 ) and were found in the insertion regions, suggesting that the T4SS may play important roles in the pathogenicity of QT520. The T6SS, which is associated with cytotoxic effectors ( Costa et al, 2015 ; Unterweger et al, 2014 ), translocates toxic effector proteins into eukaryotic and prokaryotic cells and has a pivotal role in pathogenesis and bacterial competition ( Ho, Dong & Mekalanos, 2014 ; Zoued et al, 2014 ), and this system was also reported in the pathogenic Vibrio harveyi strains ZJ0603 and CAIM 1792 ( Huang et al, 2012 ; Espinoza-Valles et al, 2012 ). This secretion system functions as a group of toxin proteins by transporting various bacterial effectors into eukaryotic cells, resulting in host cell death ( Costa et al, 2015 ), and its presence suggests that QT520 is a highly virulent strain based on our genome analysis.…”
Section: Discussionmentioning
confidence: 99%